Clean synthesis using porous inorganic solid catalysts and supported reagents - Clark, James H. (RSC clean technology monographs., 2000)
Waste minimisation has a number of aims which include enhancing the intrinsic selectivity of any given process, providing a means of recovering reagents in a form which allows easy regeneration and the replacement of stoichiometric processes with catalytic ones. Solids, as catalysts or as supports for other reagents, offer potential for benefit in all these areas. This monograph provides an overview of the properties of the more useful solid catalysts and supported reagents, and highlights their most valuable applications in the preparation of organic chemicals in liquid phase reactions. Clean Synthesis Using Porous Inorganic Solid Catalysts and Supported Reagents is concerned with the use of solid catalysts in the clean synthesis of organic chemicals. The emphasis is on chemical processes of importance to the manufacture/preparation of fine and speciality chemicals, chemical intermediates and pharmaceutical intermediates, especially where catalysis is not currently used or where current catalysts are homogeneous, leading to difficult separation procedures and unacceptable levels of waste. This book focuses on solid catalysts based on inorganic supports and covers the emerging area of chemically modified mesoporous solid catalysts.